Genetic Alterations in Medullary Thyroid Cancer: Diagnostic and Prognostic Markers - Taccaliti, A.; Silvetti, F.; Palmonella, G.; Boscaro, M. (Current Genomics, 2011)
Medullary thyroid carcinoma (MTC) is a rare calcitonin producing neuroendocrine tumour that originates from the parafollicular C-cells of the thyroid gland. The RET proto-oncogene encodes the RET receptor tyrosine kinase, with consequently essential roles in cell survival, differentiation and proliferation. Somatic or germline mutations of the RET gene play an important role in this neoplasm in development of sporadic and familial forms, respectively. Genetic diagnosis has an important role in differentiating sporadic from familiar MTC. Furthermore, depending on the location of the mutation, patients can be classified into risk classes. Therefore, genetic screening of the RET gene plays a critical role not only in diagnosis but also in assessing the prognosis and course of MTC.
Keywords: SNPs